2000
DOI: 10.1002/(sici)1097-0215(20000415)86:2<188::aid-ijc7>3.3.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

bcl-2 over-expression enhances NF-κB activity and induces mmp-9 transcription in human MCF7ADR breast-cancer cells

Abstract: bcl-2 expression is often associated with poor prognosis in several types of tumors; however, the role of this molecule in breast cancer is still controversial. We found earlier that over-expression of bcl-2 in a human breast-cancer cell line (MCF7 ADR ) enhances its tumorigenicity and metastatic potential by inducing metastasis-associated properties such as increased secretion of the matrix metalloproteinase-9 (mmp-9). In the present study, we investigated the effect of bcl-2 over-expression on the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 0 publications
4
50
0
Order By: Relevance
“…4,5,[29][30][31][32][33] Moreover, some bcl-2 protein interactors, such as the bcl-2 mitochondrial chaperone FKBP38, the orphan nuclear receptor Nur77 and the molecular chaperone HSP90, have been demonstrated to be involved in oxygen-dependent and -independent regulation of the HIF-1a protein. [33][34][35] Even if we recently demonstrated that bcl-2 protein under hypoxic conditions interacts with both HIF-1a and HSP90 proteins contributing to the enhancement of HIF-1a protein stability, 21 we cannot exclude that also other bcl-2 interactors can be involved in bcl-2-induced HIF-1a/VEGF regulation.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…4,5,[29][30][31][32][33] Moreover, some bcl-2 protein interactors, such as the bcl-2 mitochondrial chaperone FKBP38, the orphan nuclear receptor Nur77 and the molecular chaperone HSP90, have been demonstrated to be involved in oxygen-dependent and -independent regulation of the HIF-1a protein. [33][34][35] Even if we recently demonstrated that bcl-2 protein under hypoxic conditions interacts with both HIF-1a and HSP90 proteins contributing to the enhancement of HIF-1a protein stability, 21 we cannot exclude that also other bcl-2 interactors can be involved in bcl-2-induced HIF-1a/VEGF regulation.…”
Section: Discussionsupporting
confidence: 55%
“…The BH4 domain is necessary and sufficient for bcl-2 to prevent apoptosis, bind to bax, translocate into the nucleus, (a-g) TAT-CTRL (control peptide), TAT-BH4 (peptide corresponding to wild-type BH4 domain of bcl-2) and TAT-BH4mut (peptide corresponding to a mutated versions of BH4 domain into amino acids 6-7) were used reduce cell proliferation, induce nuclear factor-kappa B activity and regulate DNA repair. 4,5,28 In addition, some authors have suggested that bcl-2 deleted of its BH4 domain functions like bax to promote, rather than inhibit, cell death, 6 while other groups have reported that BH4 deletion converts bcl-2 into a dominant-negative inhibitor of bcl-2. 7 In our experimental model, the bcl-2 protein deleted of BH4 domain did not function as a dominant-negative inhibitor toward the bcl-2 ability to protect from apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Bcl-2 regulates gene expression and modulates the transactivity of several transcription factors (Feng Ricca et al, 2000;Schwarz et al, 2002;Cory et al, 2003;Quinn and Richardson, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Since a link of Bcl-2 and the NF-κB signaling pathway has been described for other cell lines [12][13][14][15]32], we examined 1) whether Bcl-2 overexpressing Jurkat cells…”
Section: Role Of Nf-κbmentioning
confidence: 99%